(3eMGVQGJ aj ebGjjS eONd ddEbJUGO, eONd dEOGQI GdCYeGd, JGQjN GdhbGFY GdEbJUGOjI, JcfhdhLjG GdeYdheGJ aj GdeDSSI, EOGQI GdeYQaI (B/s - (3GdSjO, eYjf Cejfs; (3GdSjO, Cejfs ((3GdLRGFQ(B: s (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQ(B, s, 2018)
(3JfGhd gPG GdcJGH NeS CHhGH cd HGH JVef aUhd(B: (3GdHGH GdChd(B: (3eONd ddGbJUGO hjJVef GdeTcdI GdGbJUGOjI(B, (3JYQja Yde GdGbJUGO(B, (3YdGbI Yde GdGbJUGO HGdYdhe GdCNQi(B, (3aQhY Yde GdGbJUGO(B, (3GdGbJUGO GdeYQaj(B, (3GdHWGdI, GdGSJKeGQ, GdJVNe, GdShb, GdJHGOd GdJLGQj, GdSjGSGJ GdJLGQjI CeG GdHGH GdKGfj aJVef eUQ GdaQYhfjI, GdYUhQ GdbOjeI, GdYUhQ GdhSWi, GdGacGQ GdQCSeGdjI hGdGTJQGcjI, UfOhb GdfbO GdOhdj, GdHfc GdOhdj ddGfTGA hGdJYejQ, GdJcJdGJ GdGbJUGOjI, efXeI GdJLGQI GdYGdejI,GdYhdeI, ajeG jNV GdHGH GdKGdK aJeKd aj eONd dGOGQI GdGYeGd, Yde GdGOGQI hJWhQ GdacQ GdGOGQj hGdHGH GdQGHY JcfhdhLjG GdeYdheGJ aj GdeDSSI,GdGWGQ GdYdej hGdCcGOjej JcfhdhLjG GdeYdheGJ hGdGJUGd aj GdefXeI , GeG Yf GdHGH GdSGOS GdPj abO LGA ajg GOGQI GdeYQaIs
Keywords: (3EOGQI GdCYeGds; (3EOGQI GdeYQaIs; (3GdEbJUGOs; (3GdhbGFY GdGbJUGOjI (B- (3JGQjNs